Do Parents And Social Environment Influence Stundent Understanding Of Retirement Planning? A Study On Islamic Economic And Bussines Student In Bogor - Fajar, Riski; Syamlan, Yaser Taufik (Universitas Islam Negeri Raden Intan Lampung, 2018)
ABSTRACTFinancial planning for retirement is a desire to achieve satisfaction with life in retirement. Good financial condition is a main component to having a quality life during retirement. The study aimed to find the factors influences on understanding of financial planning for retirement. Methodology that used in this study is a quantitative approach. The sample in this study as many as 350 respondents from students Islamic of economics in Bogor. Technique analysis that used in this study is Path analysis. The result in this study The results of this study indicate that in sub-structural I the variables parental influence on saving, social influence, and goal clarity have a significant influence to financial knowledge. Sub-structural II the variabel future time perspective have a significant influence to goal clarity and all variables of sub-structural III (parental influence on saving and conscientiousness) have significant infulence to future time perspective. According the result test on the sub-structural IV the variable financial knowledge have a significant influence to expectations of financial planning for retirement. On the sub-structural V there is a not significant variable, the variable is parental influence on saving to satisfaction life in retirement. Consequently, the author do a trimming on the sub-structural V to fix a structure of path model. Keywords: Financial Planning, Retirement, Retirement Planning